Basic Income Tax - Kratzke, William P. (Open textbook library., 2016)
This book is the 8th edition of a basic income tax text. This edition incorporates the Tax Cuts and Jobs Act of 2017. It is intended to be a readable text, suitable for a three-hour course for a class comprised of law students with widely different backgrounds. The text integrates several of the CALI drills that Professor James Edward Maule (Villanova University) prepared.